Evaluation of the effect of root canal preparation size and flaring on the depth of irrigant penetration (In vitro study) - Al-Sabbagh, Nada Abdulmunem; Al-Huwaizi, Hussain F (Journal of Baghdad College of Dentistry, 2013)
Background: Cleaning and shaping of root canals successfully requires high volumes of irrigation solutions that can only be applied to the apical third of root canal after enlargement with instrument, so the aim of this study was to evaluate and to compare the efficiency of Maxi-I-probe (side-vented needle), in the amount of root canal irrigant penetration for five different master apical file sizes (MAF) and four different degrees of coronal and middle thirds flaring. Materials and Methods: Two hundred resin blocks with simulated root canals were used in this study and divided into 5 major groups (40 for each) based on the size of master apical files (#20, #25, #30, #35, and #40). Each major group was subdivided into 4 subgroups depending on different sizes and depth of flaring (10 for each).The instrumentation and flaring techniques were used as following: 1. without flaring group, root canal shape resembles shape of the master apical K-file, 2. flaring I group, flaring done with Gates Glidden I for 2 mm coronally, 3. flaring II group, flaring was done with Gates Glidden I for 4 mm coronally, Gates Glidden II for 2 mm, 4. flaring III group, flaring was done with Gates Glidden I for 6mm,Gates Glidden II 4mm and Gates Glidden III for 2 mm coronally. Irrigation was done with Max-i-probe gauge 28. Results: By comparing the five different master apical file sizes at four different degrees of flaring, there was an increase in the amount of irrigant penetration with increase MAF size, taper had more effect in small canals size and decreased with further enlargement of master apical file size until no benefit was achieved in large canals size. Conclusions: It was shown that, Max-i-probe had a limited amount of irrigant entrance. Flaring was more effective in small canals than the larger canals in an amount of irrigant entrance; increasing MAF size was effective in an increase amount of irrigant entrance.